Tick-borne diseases and autoimmunity: A comprehensive review (2018)
Tick-borne diseases (TBDs) are emerging and reemerging diseases transmitted by ticks, which portray wide heterogeneity and global distribution. TBDs may present acute clinical pictures that resemble those of autoimmune diseases (i.e., musculoskeletal symptoms, cutaneous involvement, neurologic impairment, renal failure, etc.), and in some cases infection is considered a triggering factor for autoimmunity (e.g., rheumatoid arthritis, autoimmune thyroid disease, vasculitides). The clinician should consider TBDs among the differential diagnoses when approaching autoimmune-like signs in areas of tick infestation. Epidemiological setting (e.g., endemic areas, seasons) and an accurate diagnostic approach (i.e., clinical history, physical examination and laboratory tests) are necessary to confirm TBDs. Further, control and prevention of TBDs is warranted. Research in the fields of ticks microbiome and vaccination (i.e., wildlife and humans) are ahead to control vector transmission and bacterial infection. This review offers a comprehensive update on TBDs and their relationship with autoimmunity. © 2017 Elsevier Ltd